Malignant syphilis in human immunodeficiency virus-infected patients - Wei-Ting Chang; Tsung-Ting Hsieh; Yu-Hung Wu (Wolters Kluwer Medknow Publications, 2015)
Syphilis, the "great imitator" of skin diseases, remains a public health problem worldwide. Coinfection by the human immunodeficiency virus (HIV) and syphilis is common and has important clinical consequences. HIV infection may alter the classical clinical course and manifestations of syphilis. We herein report two young men who presented with fever and generalized ulceronecrotic lesions, which mimic hemorrhagic chicken pox, eczema herpeticum, or vasculitis. Malignant syphilis (lues maligna) was diagnosed according to clinical presentation, serology, and pathology. HIV infection was subsequently confirmed later. Excellent resolution of skin lesion was achieved after appropriate antibiotics therapy.